Simulation Water Level Control in The Steam Drum of Steam Power Plant's Boiler System Using A Robust Self-Tuning Scheme for PID-Type Fuzzy - Ali Fatoni; Imam Arifin; Mughny Indra Darmawan (JAREE (Journal on Advanced Research in Electrical Engineering), 2019)
The water level in the steam drum needs to be kept constant at a certain point. Therefore, control is needed for the flow rate of incoming water feedwater to adjust to the disruption of the steam flow rate that comes out. The size of the steam flow rate that comes out depends on the load demand. If the demand for loads is high and fluctuations, then the water level in the steam drum will be more difficult. The PID type fuzzy logic controller with a robust self-tuning scheme will be implemented in the water level regulation system in the steam drum. In the three-element control scheme, when given a high load of 700 MW the system produces an error deviation of 15.69 mm peak against the set point. This value is smaller than the single-element control scheme by producing an error deviation of 18.5 mm against the set point. However, when given a set point change of 40 mm the three-element control scheme produced a response of 16.82 mm peak error error to the set point. This value is greater than the system response with the single-element control scheme which only produces an error deviation of 3.91 mm peak against the set point.Keywords: fuzzy-PID, robust self-tuning scheme, steam drum.